USING ADAS INTELLIGENT SYSTEM TO HELP DRIVERS - Nasirov Ilham Zakirovich; Soliev Boburjon Abdiraim Coals (Journals Park Publishing, 2022)
Currently, the number of deaths and injuries as a result of road traffic accidents is growing every year. Setting such an ambitious goal to reduce road traffic deaths is an important step in improving road safety.
Keywords: transport; safety; injuries